Independence and Competence on Audit Fraud Detection: Role of Professional Skepticism as Moderating - Kartim, Sutisman, M.Y.Noch, Muhdi B. H. Ibrahim, M.A. Akbar (Jurnal Akuntansi, 2022)
We conducted this study to analyze and examine the effect of competence auditor independence on fraud detection. This study also analyzes the effect of competence auditor independence on fraud detection if moderated by professional skepticism. This study involved 59 auditors working at the Inspectorate of South Sulawesi Province. This sample selection uses the census method because the population is less than 100 people. We use primary data by providing questionnaires/statement sheets to respondents. The data analysis method uses the Smart PLS approach. The results showed that competence and auditor independence variables positively and significantly affected fraud detection. The auditor competence variable has a negative and significant effect on fraud detection if moderated by professional skepticism. The auditor competence variable positively and significantly affects fraud detection if moderated by professional skepticism.